Biosintesis dan Karakterisasi Nanopartikel Seng Oksida (ZnO-NPs) Menggunakan Ekstrak Daun Kenitu (Chrysophyllum cainito L.) - Syamsul Arifin, Fawaid; Nazriati (Talenta Publisher (Universitas Sumatera Utara), 2022)
Nanoparticles are materials that have superior properties compared to similar materials that are larger in size when used as raw materials. One of the nanoparticles that is trending and has many applications is zinc oxide nanoparticles (ZnO-NPs). This study aimed to synthesize ZnO-NPs using kenitu leaf extract (Chrysophyllum cainito L.) and determine the effect of extract composition and pH on the size of ZnO-NPs. Kenitu leaf extract can prevent agglomeration in the synthesis of nanoparticles because it contains secondary metabolites such as antioxidants and polyphenols. ZnO-NPs were synthesized using green method by reacting kenitu leaf extract with zinc sulfate. The success of the synthesis was indicated by the similarity of the peaks of the synthesized compounds to the standard peaks of ZnO in X-Ray Diffraction (XRD) analysis and supported by the presence of Zn-O vibrations in the 405-768 cm-1 region in Fourier Transform Infra-Red (FTIR) analysis. Analysis of UV-Vis spectra showed that ZnO-NPs were relatively stable at wavelength of 308-330 nm with an absorption peak at 317 nm and a bandgap energy of 3.25 eV. The results of FTIR characterization showed the presence of vibrations of the carbonyl and hydroxy groups in kenitu leaf extract. The results of the Scanning Electron Microscope (SEM) Â characterization showed that the ZnO-NPs synthesized using 10 mL kenitu leaf extract at pH 7 with 0.15 M zinc sulfate had predominantly spherical shape with a size of 14.10 nm. Based on experiment result addition of kenitu leaf extract may reduce the size of ZnO-NPs, while increase of mixture pH during formation reaction of ZnO-NPs may increase the size of ZnO-NPs.